THE RELATIONSHIP BETWEEN NURSES’ KNOWLEDGE AND ATTITUDE WITH B3 WASTE MANAGEMENT IN THE INPATIENT ROOM OF SUNDARI GENERAL HOSPITAL MEDAN - Salmira, Cut Saura; Amalia, Nur (HEARTY, 2024)
Introduction: Medical waste is waste produced from infectious materials, used medical equipment, expired medicines, and others, and the amount of medical waste is expected to continue to increase every year. WHO criticizes good hospital medical waste management at 15%, but in Indonesia the disposal rate is 23.3%, containerization 20.5%, and transportation 72.7%. The purpose of the study was to determine the relationship between the knowledge and attitude of nurses and the management of hazardous and toxic waste (B3) in the inpatient room of Sundari General Hospital Medan. The research method uses a quantitative approach with a cross sectional approach. The research population is all nurses with a sample of 50 people using the total sampling technique. Data were collected by interviews using questionnaires. Data analysis uses univariate and bivariate with chi-square test. The results of the study showed that 26 people (52%) had good knowledge, 29 people (58%) had negative attitudes, and 31 people (62%) had poor waste management. The results of the chi-square test were obtained that the p-value of knowledge was 0.007 and attitude was 0.008. The conclusion is that there is a relationship between knowledge and attitude with B3 waste management in the inpatient room of Sundari General Hospital Medan. It is recommended that hospitals make policies on B3 waste management, facilitate B3 waste containers and provide socialization about waste management.